Pretending to dance - Chamberlain, Diane, 1950- (New York : St. Martin's Press, 2015)
"Molly Arnette is very good at keeping secrets. She lives in San Diego with a husband she adores, and they are trying to adopt a baby because they can't have a child on their own. But the process of adoption brings to light many questions about Molly's past and her family-the family she left behind in North Carolina twenty years before."--
Keywords: Family secrets -- Fiction; Adoption -- Fiction; Life change events -- Fiction; Psychological fiction; North Carolina -- Fiction; Domestic fiction; Psychological fiction